PEMBENTUKAN SELF STIGMA ORANG DENGAN HIV/AIDS BINAAN LEMBAGA SOSIAL MASYARAKAT LENSA SUKABUMI - Virgiawan Bagaskara; Ellya Susilowati (Jurnal Ilmiah Rehabilitasi Sosial (Rehsos), 2022)
Self-stigma is a stigma that is attached to someone with HIV-AIDS. This research is to find out the self-stigma to people who are diagnosed with HIV-AIDS who get treatment from a rehabilitation center in Sukabumi, called LENSA. The aspects which are assessed from the stages of self-stigma are awareness, acceptance, application, harm due to isolation, stereotype and discrimination. This research used a qualitative approach using a descriptive method from four people who are diagnosed positive HIV-AIDS who felt isolated. The data collection technique was using in-depth interview, observation and documentation study. The result of the research indicates that the steps which have been through by people with HIV-AIDS positive are (1) stigma awareness that is feeling negative and different about themselves; (2) acceptance that is agreeing to the given stigma because of an assumption that people's opinion is bad; (3) application and impact of self-stigma that is committing self harm, and withdrawing themselves from society. Based on these findings, it is recommended that LSM Lensa arrange a program to improve self positive images through self-help groups